2020
DOI: 10.1111/een.12948
|View full text |Cite
|
Sign up to set email alerts
|

Stingless bees (Apidae: Meliponini) seek sodium at carrion baits in Costa Rica

Abstract: 1. Many terrestrial herbivores supplement their diets with minerals. Neotropical stingless bees (Apidae: Meliponini) supplement their floral diets by visiting diverse non-floral resources such as rotting fruit and muddy water. 2. Some stingless bees also visit carrion; however, it is unknown whether bees visit carrion for minerals or for another resource. Here, we investigated the mineral preferences of stingless bees visiting carrion. 3. We deployed raw chicken baits at La Selva Biological Station in Costa Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Other species of the same genera have been previously recorded from carrion baits ( 21 ). In agreement with Dorian and Bonoan ( 22 ), we also observed Trigona fulviventris (Guérin-Méneville 1844) and Trigona ferricauda (Cockerell 1917) carrying carrion in their corbiculae. We further observed carrion in the corbiculae of P. musarum .…”
Section: Resultssupporting
confidence: 91%
“…Other species of the same genera have been previously recorded from carrion baits ( 21 ). In agreement with Dorian and Bonoan ( 22 ), we also observed Trigona fulviventris (Guérin-Méneville 1844) and Trigona ferricauda (Cockerell 1917) carrying carrion in their corbiculae. We further observed carrion in the corbiculae of P. musarum .…”
Section: Resultssupporting
confidence: 91%
“…Sodium-limited consumers are attracted to sodiumenriched resources [11]. Swallowtail butterflies 'puddle' [12], some stingless bees drink human tears [26] seek sodium in carrion [27], sweat bees obtain sodium by licking humans and cattle [28 ] and water-foraging European honeybees are attracted to sodium-enriched water [29,30]. So perhaps it is not surprising that we found that a suite of pollinators were more attracted to plants with Na-enriched nectar compared with plants without Na-enriched nectar.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that plant taxa differ in their pollen K:Na , depending on pollination syndromes [it was already suggested that concentrations of vital nutrients in zoophilous plants pollen may have been shaped by the nutritional needs of their pollinators ( Ruedenauer et al., 2019 )]; however, this possibility has yet to be investigated. Additionally, pollinivores may supplement Na from sources other than pollen to balance the overall K:Na in their progeny diets ( Dorian and Bonoan, 2020 ; Khan et al., 2021 ), especially if direct larval food is produced by adults, as with Western honey bees ( Filipiak et al., 2017 ). This can take place through, for example, cannibalistic behavior, drinking animal secreta, or puddling ( Simpson et al., 2006 ; Bänziger and Bänziger, 2010 ; Dangles and Casas, 2012 ; de la Rosa, 2014 ; Dorian and Bonoan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pollinivores may supplement Na from sources other than pollen to balance the overall K:Na in their progeny diets ( Dorian and Bonoan, 2020 ; Khan et al., 2021 ), especially if direct larval food is produced by adults, as with Western honey bees ( Filipiak et al., 2017 ). This can take place through, for example, cannibalistic behavior, drinking animal secreta, or puddling ( Simpson et al., 2006 ; Bänziger and Bänziger, 2010 ; Dangles and Casas, 2012 ; de la Rosa, 2014 ; Dorian and Bonoan, 2020 ). It is possible that a tradeoff occurs between producing low K:Na pollen for pollinators and high K:Na pollen physiologically optimizing fertilization.…”
Section: Discussionmentioning
confidence: 99%